The Efficiency of E-KTP Services at The Tubbi Taramanu Sub-District Office in Polewali Mandar Regency in Order to Realize Good Governance - Andi Nur Fiqhi Utami (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
The implementation of Good Governance can be seen as part of the effort to implement democratic principles in public services. Given the current situation in public services that requires the implementation of Good Governance to achieve good organizational goals, human resources such as bureaucracy must have the qualities and attitudes of Good Governance principles to achieve those goals. This study aims to determine the implementation of Good Governance at the Tubbi Taramanu Sub-district Office in Polewali Mandar Regency. The research design used was descriptive quantitative research. The results of this study show that the implementation of Good Governance at the Tubbi Taramanu Sub-district Office in Polewali Mandar Regency has a fairly good quality in terms of efficient public services that meet the needs and facilitate administrative services for the community. Based on the reference to the aspect of e-KTP service efficiency, it is known that the results of the study show the percentage of each efficiency indicator, which includes successful and effective (2.82%), real work distribution (3.82%), rationality of authority and responsibility (2.94%), and real work procedures (2.88%). Based on the average/overall value, each of these indicators obtained an efficiency percentage of 2.88%, which is categorized as Efficient.